An overview insight into employment of disabilities at workplaces around the world: A review of the literature - Nweiser Mishlin; Dajnoki Krisztina (Anali Ekonomskog fakulteta u Subotici)
Many people with disabilities still face difficulties and obstacles trying to secure employment. Organizations are doing more and more to improve employment opportunities for people with disabilities (PWD), because it is in their best interests, due to factors such as a dearth of skilled workers, a lack of trained workers, a rise in the prevalence of disability among their labor groups, as well as in the laws and public attitudes supporting workplace fairness and diversity. This article used a qualitative methodology and conducted a thorough evaluation of the existing literature using a variety of different databases such as Science Direct, Springer, Google Scholar, JSTOR, and Elsevier, which were used to identify various research articles related to the employment of PWD. We looked at research on the advantages of hiring people with disabilities, as well as HR management procedures with reference to recruiting persons with disabilities, and also investigated the methodology this literature used. Our findings demonstrate that the advantages of employing disabled individuals are many. To better understand how advantages may differ by disability type, industry, and work type, more research is required.